(untitled) (Raparin Journal of Humanities (RJH), 2025)
This study evaluates the current English language curriculum taught in public vocational schools across the Kurdistan Region of Iraq. The research identifies deficiencies and gaps in the English curriculum and examines how well it meets students’ needs and modern labor market demands. Employing a mixed-methods approach, data were collected through three tools: a questionnaire for students and stakeholders (400 participants), a questionnaire for vocational English teachers (43 participants from 43 public vocational schools), and semi-structured interviews with seven English supervisors and policymakers from the Ministry of Education. Quantitative data were analyzed using descriptive and inferential statistics using SPSS, whereas qualitative data were analyzed with thematic analysis to elucidate the perceptions of key stakeholders. The findings indicate several weaknesses in the curriculum’s content, structure, and practical application. Teachers, students, and policymakers all indicated that the current curriculum lacks sufficient alignment with students’ professional needs (particularly regarding speaking, listening, and writing skills, as well as the incorporation of technology) and job market demands. The study advocates for the urgent revision of the curriculum through a needs-based, negotiated syllabus that focuses on job-orientated language skills and practical communication. The findings support educational reform efforts and help vocational education in the KRI respond more effectively to evolving Kurdish market needs.